Functionalization of PET with carbon dots as copolymerizable flame retardants for the excellent smoke suppressants and mechanical properties. (January 2022) - Gu, Weiwen; Dong, Zhenfeng; Zhang, Anying; Ma, Tianyi; Hu, Qiang; Wei, Jianfei; Wang, Rui
Highlights: Gelatin-based Carbon Dots (gCDs) was successfully prepared through one-step hydrothermal process from environmental-friendly gelatin, which is a renewable natural polymer. gCDs is adopted as copolymerizable flame retardants for the preparation of flame retardant copolyester (gCDs-PET) for the first time. gCDs-PET composites have better smoke suppressant and higher flame retardancy than pristine PET. It was demonstrated that the addition of gCDs into PET could enhance the mechanical strength and gCDs-PET could be made to fibers with excellent mechanical property. Abstract: Based on the excellent flame retardant performance, environment-friendly and abundant surface functional groups, Carbon Dots (CDs) were adopted as copolymerizable flame retardants for Poly(ethylene terephthalate)(PET) for the first time. The CDs with gelatin as precursor (gCDs) were synthesized by one-step hydrothermal method and copolymerized with pure terephthalic acid (PTA) and ethylene glycol(EG) to prepare flame retardant copolyester (gCDs-PET) based on the hydroxyl and amine groups on the surface of gCDs by in situ polymerization. It is demonstrated that gCDs-PET had showed better smoke suppressant and higher flame retardancy than pristine PET. The limiting oxygen index (LOI) of gCDs-PET composites achieved to 29% with the addition of 2.0 wt% gCDs. What is more, cone calorimeter tests showed that the peak value of heat release rate(pk-HRR) greatly decreased 42.66% and the total smoke production (TSP) reduced 62.64%. Besides, the flame-retardant mechanism disclosed that gCDs catalyzes the thermal decomposition of PET to form a shielding carbon layer, which handicap the release of combustible materials to the outside and expand the as-formed char, so that interrupt the combustion reaction. Furthermore, mechanical properties and spinnability of gCDs-PET was evaluated. It was demonstrated that the addition of gCDs into PET could enhance the mechanical strength and gCDs-PET could be made to fibers with excellent spinnability.